Republic of Latvia : 2022 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economy fared relatively well during the pandemic, but the war in Ukraine is another major shock. The key vulnerabilities are Latvia's significant reliance on imported gas from Russia until recently, the impact of high international energy prices on inflation and economic activity, and refugee inflows. Thus far, almost 33,000 refugees have entered Latvia. Parliamentary elections later this year may put pressure on the government budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Latvia, Republic of